Effect of Neodymium: Yttrium-Aluminium-Garnet Laser Posterior capsulotomy on refractive status of the Eye - Kanwal Zareen Abbasi, Bilal Humayun Mirza, Mibah Munshi; Wajeeha Rasool; Ali Raza (Journal of Rawalpindi Medical College, 2021)
Objective: To assess the effect of Neodymium: Yttrium-Aluminium (Nd: YAG) laser posterior capsulotomy on the refractive status of the eye. Study Design: Quasi-experimental. Setting: Outpatient department of Benazir Bhutto Hospital, Rawalpindi. Duration: 1st January 2017 to 30th June 2017. Materials and Methods: A total of 95 eyes of 95 patients were included in this study. The patients were selected based on non - randomized convenient sampling. Among these patients 49 were females and 46 were males. The age range was 43 years to 85 years. These patients were those who had undergone uncomplicated cataract surgery with intraocular lens implantation 6 months or more than 6 months before presentation with posterior capsular opacification. Before Nd: YAG laser posterior capsulotomy, complete anterior and posterior segment examinations of these patients was performed and they were found to have no other associated anterior or posterior segment pathologies. Autorefractometre reading and best-corrected visual acuity were recorded and then after dilating the pupils, the procedure was performed. Post YAG capsulotomy, Autorefractometre readings were recorded again on the same day, at 1 week and the end of 4 weeks. Readings at the end of 4 weeks were considered for result purposes. These readings were converted into spherical equivalents for data analysis. Results: Data was analyzed through the SPSS version 18. The mean age was 60.14 years with a standard deviation of 9.241. Spherical equivalents were compared before and after YAG capsulotomy. Wilcoxon signed ranks test was applied. P-value (0.70) was found to be statistically insignificant which supported our hypothesis. Conclusion: Nd: YAG laser capsulotomy does not change the refractive status of the eye.